Effects of ultra‐high pressure on the biochemical properties and secondary structure of myofibrillar protein from Oratosquilla oratoria muscle. (19th August 2019) - Gaoshang, Li; Yanting, Chen; Shifen, Xuan; Mingchun, Lv; Jinjie, Zhang; Qiaoming, Lou; Ru, Jia; Yang, Wenge
Abstract: Oratosquilla oratoria ( O. oratoria ) were treated with 300, 350, and 400 MPa for 5, 8, and 10 min, respectively. The myofibrillar protein (MP) content, sulfhydryl content, Ca 2+ ‐ATPase activity, surface hydrophobicity and secondary structure of MP were determined to investigate the effects of ultra‐high pressure (UHP) on the biochemical properties and secondary structure of MP from O. oratoria muscle. Results showed that the relatively low pressures have no significant effects on the MP content. When the pressure and holding time increased, the MP content decreased significantly. However, when the pressure condition reached 400 MPa for 10 min, the relative sulfhydryl content and Ca 2+ ‐ATPase activity reduced to 62.76 and 47.88%, respectively, while the relative surface hydrophobicity increased to 132.20%. Moreover, as pressure increased, the β‐Turn and α‐Helix gradually converted to β‐Sheet and Random coil of MP. In short, the biochemical properties and secondary structure of MP from O. oratoria had significant correlations and they interacted with each other. These findings can provide a reference for using UHP to assist the shelling of O. oratoria . Practical applications: UHP is an emerging food processing technology that is widely used in the processing of aquatic products, such as shelling. While whether the choice of conditions will affect the meat quality of shelled aquatic products is still less studied. The purpose of this study was to investigate the effects of different UHP parameters on the biochemical characteristics and structure of myofibrillar protein in O. oratoria, and to determine the effects on the quality of O. oratoria meat. These results could provide theoretical guidance for determining the more suitable parameters of UHP, which was conducive to the development of O. oratoria products and the application of UHP technology in aquatic products processing. Abstract :